2004
DOI: 10.1021/jm034180+
|View full text |Cite
|
Sign up to set email alerts
|

New Class of Corticotropin-Releasing Factor (CRF) Antagonists:  Small Peptides Having High Binding Affinity for CRF Receptor

Abstract: The discovery of small and potent peptide antagonists of the corticotropin-releasing factor (CRF) receptor is described. Through the structure-activity relationship studies of 12-amino acid peptide corresponding to the C-terminal residues of astressin, we assumed that a particular surface of the alpha-helix was important for binding to the receptor. The small peptide containing d-Ala31 and cyclohexylalanine38 on that surface was as potent as astressin in binding to the CRF receptor and showed significant ACTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 13 publications
2
49
0
2
Order By: Relevance
“…and CRH 2 receptors (Grigoriadis 2005;Yamada et al 2004). X = cyclohexyl alanine; f = Dphenylalanine; EAEK = lactam bridge.…”
Section: Both Crh and Ucn Have High Affinities For The Crh-binding Prmentioning
confidence: 99%
“…and CRH 2 receptors (Grigoriadis 2005;Yamada et al 2004). X = cyclohexyl alanine; f = Dphenylalanine; EAEK = lactam bridge.…”
Section: Both Crh and Ucn Have High Affinities For The Crh-binding Prmentioning
confidence: 99%
“…They are antagonists because they occupy the major binding site, thus blocking agonist binding, but they cannot induce receptor signaling because the first eight residues are absent. Such peptide antagonists are astressin (42) and the short CRF-based analogs comprising residues 30-41 (9), which bind to the ECD1 of CRF-R1 in a similar conformation as astressin (Fig. 1B and SI Table 3) (33).…”
Section: Crf Ligand-receptor Interactions Have a Common Binding Modementioning
confidence: 99%
“…These belong to the peptide hormone B1 family (family B1 GPCRs), comprising receptors for growth hormone releasing factor, secretin, calcitonin, vasoactive intestinal peptide, glucagon, glucagon-like peptide-1, and parathyroid hormone. Two CRF receptors, CRF-R1 and CRF-R2, have been cloned in mammals (6, 7).Structure activity studies of CRF showed that the first eight N-terminal residues of the hormone are necessary for GPCR signaling (1, 8), whereas the C-terminal (Ϸ15) residues are important for binding (9,10). A two-domain behavior for ligand binding was also observed for the receptors (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yamada et al described a twelve amino acid long peptide antagonist based on the C-terminus of CRH, indicating that this short C-terminal sequence is enough for binding the extracellular domain of the CRHR 1 (CRHR 1 -ECD1) (Yamada et al 2004).…”
Section: Peptide Antagonistsmentioning
confidence: 99%